More than a communication disorder: inequities in the financial toxicity of post-stroke aphasia - Jacobs, Molly; Ellis, Charles (Frontiers in Stroke, 2025)
IntroductionAphasia, a communication disorder often resulting from stroke, can have profound impacts on both health outcomes and financial wellbeing. While the physical and cognitive consequences of stroke are well documented, the financial strain, or “financial toxicity,” associated with managing chronic conditions like aphasia remains underexplored. Furthermore, financial toxicity is not experienced equally across racial and ethnic groups, with disparities driven by socioeconomic factors, access to healthcare, and structural inequities. This study compares the financial toxicity of people with aphasia (PWA) to those with stroke alone, examining differences across racial and ethnic groups to highlight disparities in economic burden.MethodsThis study utilized data from the Medical Expenditure Panel Survey (MEPS) collected between 2018 and 2021 to examine the financial toxicity of PWA compared to those with stroke only. Financial toxicity was assessed using self-reported income and wealth data from the MEPS. Individual-level income and wealth values were calculated from the self-reported financial data to quantify the financial burden. Fixed effects regression models were employed to account for unobserved individual heterogeneity, controlling for time-invariant characteristics. Interaction terms were included in the models to capture the differential financial impacts of aphasia on Black and Hispanic individuals, compared to other racial and ethnic groups. The analysis examined both within-group and between-group differences in financial toxicity, highlighting potential racial and ethnic disparities among those affected by aphasia.ResultsApproximately 18.71% (N = 281) of respondents who reported having a stroke also had aphasia. After controlling for demographic, health, and household characteristics, PWA had 21% lower income and 7% lower wealth compared to stroke survivors without aphasia. Aphasia had a disparate impact on the income (−29%) and wealth (−24%) of Black stroke survivors. These findings were consistent across different model specifications, highlighting the robustness of the results indicating racial inequity in the financial toxicity of post-stroke aphasia.ConclusionThis study showed the financial impact of post-stroke aphasia and the disparate burden among Black PWA. The findings highlight the need to address the financial ramifications of post-stroke morbidities such as aphasia among vulnerable populations.